Influence of School Heads’ Motivational Practices on Teachers’ Job Satisfaction in Public Secondary Schools in Igunga District, Tabora –Tanzania - Pascal, Rachel; Tangi, Felista (International Journal of Humanities and Education Development (IJHED), 2022)
Teacher’s job satisfaction is one of the areas in enhancing student’s academic performance which calls for school management attention for the school progress because the development of any school depends much on teacher’s satisfaction. This study aim was to investigate the influence of school heads’ motivational practices on teachers’ job satisfaction in public secondary schools at Igunga District, Tanzania. The study is guided by the Herzberg’s two factor theory of motivation. Convergent parallel research design which included mixed research approach was employed. The study used sample size of 99 respondents whereby questionnaire was used to collect data from teachers and interview guides was used to collect data from the district secondary education officer, ward education officers and the school heads. Quantitative data were analyzed using SPSS version 23 and qualitative data were analyzed through thematic data analysis. Findings from the study revealed that, school heads’ motivational practices such as job recognition, has an influence on teachers’ job satisfaction. The study further recommended that, all school heads should motivate their teachers in order to enhance their job satisfaction.